The Acute Effects of Changes to AV Delay on Blood Pressure and Stroke Volume: Potential Implications for Design of Pacemaker Optimization Protocols - Manisty, Charlotte H. (2011)
BACKGROUND: Atrioventricular (AV) delay optimization of biventricular pacemakers (cardiac resynchronization therapy, CRT) may maximise hemodynamic benefit, but consumes specialist time to conduct echocardiographically. Non-invasive blood pressure monitoring is a potentially-automatable alternative, but it is unknown whether it gives the same information, and similar precision (signal-to-noise ratio). Moreover, the immediate blood pressure increment on optimization has been reported to decay away: it is unclear whether this is the result of an (undesirable) fall in stroke volume or a (desirable) compensatory relief of peripheral vasoconstriction. METHODS AND RESULTS: To discriminate between these alternative mechanisms, we measured simultaneous beat-to-beat stroke volume (flow) using Doppler echocardiography, and blood pressure (BP) using finger photoplethysmography, during and after atrioventricular delay changes from 40 to 120 ms in 19 subjects with cardiac pacemakers. BP and stroke volume both increased immediately (p<0.001, within one heartbeat). BP showed a clear decline a few seconds later (average rate −0.65mmHg/beat, r=0.95 [95% CI 0.86 to 0.98]); in contrast, stroke volume did not decline (p=0.87). The immediate BP increment correlated strongly with the stroke volume increment (r=0.74, p<0.001). Signal-to-noise ratio was threefold better for BP than stroke volume (6.8±3.5 versus 2.3±1.4, p<0.001). CONCLUSIONS: Improving atrioventricular delay immediately increases blood pressure, but the effect begins to decay within a few seconds. Reassuringly this is due to compensatory vasodilatation rather than reduction in cardiac function. Pacemaker optimization will never be reliable unless there is adequate signal-to-noise ratio. Using BP rather than Doppler minimises noise. The early phase – before vascular compensation – has the richest signal lode.